ANALISIS PENERAPAN PERATURAN PEMERINTAH NO 46 TAHUN 2013 PADA BESARNYA PAJAK PENGHASILAN - Haryati, Ayu Putu Mirah; Noviari, Naniek (E-Jurnal Akuntansi, 2016)
This study conducted to determine the application of PP No. 46 Year 2013 on the amount of income tax PT XYZ in Fiscal Year 2014 and 2015, comparison of income tax payable by PT XYZ both before and after this rule is applied. This study uses comparative descriptive analysis techniques. The results showed for 2014 there are errors in the determination of gross income and the determination of income tax owed ??for each month , whereas for 2015 the calculation of the company with calculation of PP No. 46 Year 2013 compliant. PT XYZ in paying income tax due more to gain if using the general provisions of the Income Tax Act compared using PP No. 46 Year 2013. This is due in 2014 and 2015 PT XYZ suffered fiscal losses and can compensate for the losses in next year, if not required use PP No. 46 Year 2013.
Keywords: income tax, the application of government regulations